Numerical and experimental investigation on hydrodynamic performance of the stick-held dip net in Pacific saury fishery - Li, Fei; Song, Liming; Hua, Chuanxiang; Zhu, Qingcheng (Frontiers in Marine Science, 2022)
Stick-held dip (SHD) net is an effective fishing gear target for catching the Pacific saury. In this study, the hydrodynamic performance of an SHD net in current was investigated by means of numerical simulation and experimental test, and a mathematical model based on the lumped-mass method and principle of rigid body kinematics was developed to predict the net shape and tension of the cable. A series of physical model tests based on Tauti’s law and full-scale measurements at sea were conducted to evaluate the applicability of the numerical model. The results showed that the prediction performance of the numerical model was good, with a mean relative error of approximately 20% among the numerical, experimental, and field measured data. The dynamic shooting behavior of the SHD net at different current velocities and the effects of the length of the hauling rope and the mesh size on the net shape and tension of the cable were analyzed using the numerical simulation approach. When the current velocity increased from 0.12 to 0.46 m/s, the enclosed volume of the SHD net decreased by 62.9%. The height of net opening increased by 9.29% to 13.53% for every 10% increase in the length of the hauling rope from 0.96 to 1.44 m. With the increase in mesh size from 24 to 30 and 35 mm, the sinking depth and speed of the net increased, and the tension force of the cables decreased by 9.02% and 12.10%, respectively. The results suggested that (1) the numerical model could realistically represent the hydrodynamic characteristics of the SHD net; (2) the suitable operation current velocity is below 0.60 m/s; (3) the reasonable length of the hauling rope is about 30 m; and (4) the mesh size of the main netting could be increased to 30 mm.